1991
DOI: 10.1071/rd9910699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of season, GnRH administration and lupin supplementation on the ovarian and endocrine responses of merino ewes treated with PMSG and FSH-P to induce superovulation

Abstract: Administration of gonadotrophin releasing hormone (GnRH) 24 h after sponge withdrawal did not affect the numbers of corpora lutea (CL) or persistent large follicles (LF) in ewes superovulated with 400 I.U. pregnant mare serum gonadotrophin and 12 mg follicle stimulating hormone in spring (11.6 +/- 0.9 v. 13.0 +/- 0.9 CL and 0.8 +/- 0.9 v. 0.9 +/- 0.3 LF, for +GnRH and -GnRH ewes, respectively). However, it did increase the ovulatory response of ewes superovulated in autumn (15.8 +/- 1.2 v. 11.8 +/- 1.1 CL). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
4
17
2
Order By: Relevance
“…Similar results have been reported in ewes [10] and goats [11]. However, prematurely regressed CL has been observed in suprovulated ewes [12][13][14], cows [15] and goats [16][17][18]. Ryan et al [13] reported that the proportion of ewes that ovulated and subsequently had M chorionic gonadotropin (eCG) has been conventionally used for superovulation in ewes [1][2][3][4].…”
supporting
confidence: 65%
See 3 more Smart Citations
“…Similar results have been reported in ewes [10] and goats [11]. However, prematurely regressed CL has been observed in suprovulated ewes [12][13][14], cows [15] and goats [16][17][18]. Ryan et al [13] reported that the proportion of ewes that ovulated and subsequently had M chorionic gonadotropin (eCG) has been conventionally used for superovulation in ewes [1][2][3][4].…”
supporting
confidence: 65%
“…Jabbour et al [12] and Ryan et al [13] reported that more ewes had regressed CL in autumn (24% and 37%, respectively) than in spring (6% and 21%, respectively). In their reports, 12 or 18 mg pFSH was administered with multiple injections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inadequate luteal function has also been reported in superovulated ewes following oestrous synchronization using a dual prostaglandin injection treatment (Trounson et al, 1976;Schiewe et al, 1991). In embryo donor ewes, the incidence of premature luteal regression after a progestagen protocol and superovulation seems to be higher in the seasonal anoestrus than in the breeding season, even at temperate latitudes (Jabbour et al, 1991;Ryan et al, 1991). Corpora lutea from ewes undergoing premature luteolysis have a reduced population of small luteal cells compared to normal corpora lutea (Schiewe et al, 1991).…”
Section: Luteal Activitymentioning
confidence: 99%